Developing software to assess the seismic risk of natural gas infrastructure: OpenSRA - Largent, Micaela; Bray, Jonathan; Watson-Lamprey, Jennie; Abrahamson, Norman (Frontiers in Built Environment, 2023)
Using risk-informed decisions prior to a seismic event enables utility owners to proactively and cost-effectively maintain infrastructure. As part of a multi-year study, the Pacific Earthquake Engineering Research (PEER) center in conjunction with Lawrence Berkeley National Laboratory (LBNL), the NHERI SimCenter at Berkeley, Slate Geotechnical Consultants (Slate), and several subcontractors, developed an open-source seismic risk analysis (OpenSRA) program that implements the performance-based earthquake engineering (PBEE) risk framework using a user-friendly interface, capable of operating on a desktop computer. This effort is made up of two elements: 1) research of seismic demand and capacity models, laboratory testing, and finite element modeling, and 2) implementing these findings into a backend calculation program with an easy-to-use interface. The NHERI SimCenter, Slate Geotechnical Consultants, and PEER researchers developed an integrative method to create an efficient code with a useful interface. OpenSRA implements and updates current models addressing different forms of seismically induced ground deformation (e.g., fault rupture, liquefaction, and landslide) as well as ground shaking. It quantifies resistance to deformation in buried pipelines, well heads, caprocks, and surficial elements, and then provides a framework for estimating the uncertainty in both the models and parameters. The software allows the end-user to utilize these models according to the resolution of the available data (i.e., state-wide, regional, or site-specific). The interface provides a visualization of the inputs (e.g., ground motion, and potential to liquefy) and outputs (risk of leaks/breaks) overlaid on different maps of California (e.g., satellite, topographic, and geologic). OpenSRA provides the industry with updated seismic demand and capacity models, an efficient calculation method, and user-friendly software.